2021
DOI: 10.1002/cam4.4362
|View full text |Cite
|
Sign up to set email alerts
|

Muscle weakness as an additional criterion for grading sarcopenia‐related prognosis in patients with cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…HGS is an inexpensive and simple measurement method that can be used in clinical practice [8]. HGS has been reported to be a valuable prognostic factor and can provide important additional prognostic information for malignancies [16,17]. However, muscle mass and strength differ depending on the patient's body size, which means that HGS needs to be standardized to better assess the impact of HGS on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…HGS is an inexpensive and simple measurement method that can be used in clinical practice [8]. HGS has been reported to be a valuable prognostic factor and can provide important additional prognostic information for malignancies [16,17]. However, muscle mass and strength differ depending on the patient's body size, which means that HGS needs to be standardized to better assess the impact of HGS on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between body composition and pharmacokinetics of chemotherapy is also well established [ 45 ]. Recently, Cereda et al demonstrated that muscle weakness was a better predictor of survival than skeletal muscle mass estimated by bioelectrical impedance analysis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 In particular, it has been observed that handgrip strength assessment is a reliable survival predictor associated with body composition variations, being also a good indicator of functional capacities in chronic diseases. 9 In oncology, low handgrip strength levels are associated with fatigue, impaired QoL, treatment-related toxicity and higher mortality. 10 11 National and international guidelines on clinical nutrition in oncology-including those issued by the Italian Ministry of Health in 2017 12 -underline the utility of early evaluation of nutritional status in patients with cancer and of a prompt and appropriate nutritional support, whenever indicated, in order to prevent or treat malnutrition, improve patients' clinical outcomes and QoL, and increase the efficacy and tolerability of cancer treatments.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Sarcopenia (ie, the loss of skeletal muscle (SM) and strength) is the main issue which contributes to functional deterioration in patients with cancer 8. In particular, it has been observed that handgrip strength assessment is a reliable survival predictor associated with body composition variations, being also a good indicator of functional capacities in chronic diseases 9. In oncology, low handgrip strength levels are associated with fatigue, impaired QoL, treatment-related toxicity and higher mortality 10 11…”
Section: Introductionmentioning
confidence: 99%